Cut core and noise suppression member using the same

The cut core design with a specific soft magnetic alloy composition and surface oxide layer addresses the issue of rust-induced magnetic permeability loss, maintaining stable performance in challenging environments.

JP7649436B1Active Publication Date: 2025-03-19RIKEN CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2025505902
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-09-29
Filing Date
2024-09-26
Publication Date
2025-03-19
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

Cut cores experience reduced magnetic permeability due to rust formation on the contact surface, which is exacerbated by the decomposition of adhesives during heat treatment and the difficulty in maintaining surface oxide films.

Method used

A cut core structure featuring laminates with a specific soft magnetic alloy composition, including a substrate, an intermediate diffusion layer, and a surface oxide layer, which enhances corrosion resistance and maintains magnetic properties even in harsh environments.

Benefits of technology

The proposed solution effectively prevents rust on the contact surface, ensuring stable magnetic permeability over a long period, even in high-temperature and high-humidity conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649436000006
    Figure 0007649436000006
  • Figure 0007649436000007
    Figure 0007649436000007
  • Figure 0007649436000008
    Figure 0007649436000008
Patent Text Reader

Abstract

The present invention provides a means for stably maintaining the magnetic properties of a cut core for a long period of time even when it is difficult to provide a surface oxide film on the contact surface of the cut core by heat treatment at a crystallization heat treatment temperature. The cut core according to the present invention comprises two or more laminates in which soft magnetic alloy ribbons are laminated in the thickness direction, each laminate having at least one contact surface, the laminates being in contact with each other at the contact surfaces, and the soft magnetic alloy ribbons are made of Fe 100-x-y-z-a-b S x B y Cu z Cr a M b (wherein M represents at least one element selected from Nb and Mo, and x, y, z, a, and b represent the atomic percentages of Si, B, Cu, Cr, and M, respectively, and satisfy 11.0≦x≦17.0, 5.0≦y≦10.0, 0.5≦z≦2.0, 0.5≦a≦4.0, 1.0≦b≦5.0, and 65≦100-xyzab≦75.)
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a cut core and a noise suppression member using the same. [Background technology]

[0002] A magnetic core is a ring-shaped or rod-shaped member made of a soft magnetic material. Magnetic cores are used in transformers and reactors in combination with coils to increase magnetic permeability, and are also used as noise filters placed around cables. Soft magnetic materials used for magnetic cores include ferrite, silicon steel sheets, and soft magnetic alloy ribbons. Silicon steel sheets and soft magnetic alloy ribbons are often used in the form of laminates wound into a ring shape and stacked in the thickness direction.

[0003] Patent Document 1 describes an invention of a magnetic core called a cut core, which has a structure in which a soft magnetic alloy ribbon made of an Fe-based nanocrystalline alloy is wound and at least a part of the magnetic path is cut. Cut cores are widely used because they are convenient for placing around a wired cable as a noise countermeasure member or for use in combination with a manufactured coil. Patent Document 1 describes that by polishing the cut surface of the cut core and then etching it to remove burrs on the cut surface, conduction in the stacking direction of the laminate is prevented, and a cut core with low hysteresis loss is obtained.

[0004] On the other hand, attempts have been made to improve the corrosion resistance of soft magnetic alloy ribbons. For example, Patent Document 2 describes an invention of a soft magnetic alloy with excellent corrosion resistance obtained by heat treating an amorphous alloy containing 2 to 5 atomic % of Cr. Patent Document 3 describes an invention of a soft magnetic alloy ribbon with excellent corrosion resistance in which an oxide film is formed on the surface by heat treating a primary microcrystalline alloy ribbon in an atmosphere having an oxygen concentration of 6 to 18%. The heat treatments described in Patent Documents 2 and 3 are both performed for the purpose of precipitating microcrystals in the alloy ribbon. The heat treatment temperature is 550°C in Patent Document 2 and 420°C in Patent Document 3. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 9-27412 [Patent Document 2] Japanese Patent Application Publication No. 3-24252 [Patent Document 3] JP 2011-149045 A Summary of the Invention [Problem to be solved by the invention]

[0006] In cut cores, the cut surfaces of the laminates serve as contact surfaces, and adjacent laminates come into close contact with each other via the contact surfaces, resulting in a magnetic connection. However, if rust occurs on the contact surfaces, the volume of the rust expands, creating gaps on the contact surfaces, which can disrupt magnetic continuity and significantly reduce the magnetic permeability of the entire cut core. For this reason, special care must be taken to prevent rust from occurring on the contact surfaces of cut cores.

[0007] Patent Documents 2 and 3 disclose findings on the corrosion resistance of soft magnetic alloy ribbons having a surface oxide film formed by heat treatment for the purpose of precipitating microcrystals in the alloy ribbon. On the other hand, in the contact surface of the cut core disclosed in Patent Document 1, the surface oxide film formed by heat treatment is peeled off by processing, resulting in the formation of a contact surface without a surface oxide film. The findings disclosed in Patent Documents 2 and 3 cannot be applied to the corrosion resistance of such a contact surface without a surface oxide film.

[0008] In the manufacturing method of cut cores described in Patent Document 1, a laminate formed by winding an alloy ribbon is subjected to a crystallization heat treatment, and then the laminate is impregnated with an adhesive and fixed. The heat resistance temperature of the adhesive is lower than the temperature of the crystallization heat treatment. If the laminate is cut after being fixed with an adhesive, and then heat treated again at the temperature of the crystallization heat treatment in order to provide a surface oxide film on the contact surface formed by the processing, a new problem occurs in that the adhesive fixing the laminate is decomposed by heat.

[0009] On the other hand, when cutting and crystallization heat treatment are performed prior to fixing the laminate by impregnation with adhesive, the laminate is cut while not fixed with adhesive, which may result in other problems, such as the cutting process being unable to be performed accurately or the position of the alloy ribbon shifting during fixing, compromising the flatness of the contact surface.

[0010] The present invention has been made in consideration of these problems specific to cut cores, and aims to provide a cut core that can maintain stable magnetic properties for a long period of time, even when it is difficult to provide a surface oxide film on the contact surface of the cut core by heat treatment at the crystallization heat treatment temperature. [Means for solving the problem]

[0011] The gist and configuration of the present invention are as follows.

[0012] [1] A cut core having two or more laminates in which soft magnetic alloy ribbons are laminated in the thickness direction, The laminates each have at least one contact surface, and are in contact with each other at the contact surfaces; The soft magnetic alloy ribbon is Fe 100-x-y-z-a-b S x B y Cu z Cr a M b (wherein M represents at least one element selected from Nb and Mo, x, y, z, a, and b represent the atomic percentages of Si, B, Cu, Cr, and M, respectively; 11.0≦x≦17.0, 5.0≦y≦10.0, 0.5≦z≦2.0, 0.5≦a≦4.0, 1.0≦b≦ 5.0 And 65≦100-xyzab≦75 is satisfied.) The composition is represented by A cut core characterized by:

[0013] [2] At the contact surface, the soft magnetic alloy ribbon includes: a substrate having the above-mentioned composition; an intermediate diffusion layer located outside the substrate, in which Si is enriched and Fe is depleted compared to the composition of the soft magnetic alloy ribbon; and a surface oxide layer located outside the intermediate diffusion layer, in which O is newly contained, Si is enriched, and Fe and Cr are depleted compared to the composition of the soft magnetic alloy ribbon. The cut core described in [1] above.

[0014] [3] The soft magnetic alloy ribbon contains an Fe-based nanocrystalline alloy. The cut core described in [1] or [2] above.

[0015] [4] The oxygen concentration at the outermost surface of the surface oxide layer is 43.0 atomic % or more; The cut core described in [3] above.

[0016] [5] The impedance at a frequency of 100 kHz is measured before and after immersing the cut core in ion-exchanged water for 100 hours, and the measured value before immersion is Z A , the measured value after immersion is Z B Then, (Z B -Z A ) / Z A The absolute value of the impedance change rate ΔZ calculated by × 100 is 15% or less. A cut core according to any one of [1] to [4] above.

[0017] [6] A ring-shaped body formed by winding the soft magnetic alloy ribbon into a ring shape is cut at n locations (where n is an integer of 2 or more) perpendicular to the circumferential direction of the ring-shaped body, and n laminates are formed by cutting the n laminates into (n×2) planes as the contact surfaces, and two adjacent laminates among the n laminates are in contact with each other at the cut surfaces as the contact surfaces, thereby forming a magnetic circuit as a whole. A cut core according to any one of [1] to [5] above.

[0018] [7] For one annular body formed by winding the soft magnetic alloy ribbon into a ring shape, there are provided two or more laminates formed by providing one discontinuous portion in a part of the circumferential direction of the annular body, at least one of two widthwise end faces of each of the two or more laminates is the contact surface, and two adjacent laminates of the two or more laminates are in contact with each other at the widthwise end face as the contact surface so that the respective discontinuous portions do not overlap in the circumferential direction, thereby forming a magnetic circuit as a whole. A cut core according to any one of [1] to [5] above.

[0019] [8] Using the cut core described in any one of [1] to [7] above, Noise suppression material. Effect of the Invention

[0020] According to the present invention, rust is less likely to occur on the contact surface of the cut core than in the prior art, and therefore it is possible to prevent a decrease in the magnetic permeability of the cut core over a long period of time even in a rust-prone environment such as high temperature and high humidity. [Brief description of the drawings]

[0021] [Figure 1] 1 is a graph showing the relationship between the distance from the surface of a contact surface of a soft magnetic alloy ribbon after polishing without heat treatment for crystallization and the ratio of elements. [Diagram 2]1 is a graph showing the relationship between the distance from the surface and the ratio of elements in a contact surface of a soft magnetic alloy ribbon containing an Fe-based nanocrystalline alloy that has been subjected to heat treatment for crystallization and then polished. [Diagram 3] 1 is a graph showing the relationship between the distance from the surface and the ratio of elements in the contact surface of a soft magnetic alloy ribbon containing an Fe-based nanocrystalline alloy, which was subjected to heat treatment for crystallization, polished, and then heated in air at 130°C for 8 hours. [Figure 4] FIG. 2 is a schematic diagram showing an example of one embodiment of a cut core. [Diagram 5] 10A to 10C are schematic diagrams showing examples of other embodiments of the cut core. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Hereinafter, an embodiment of the present invention will be described in detail.

[0023] [Cut core] In one embodiment, the present invention relates to a cut core, which includes two or more laminates in which soft magnetic alloy ribbons are laminated in a thickness direction, and each laminate has at least one contact surface, and the laminates are in contact with each other at the contact surfaces.

[0024] The soft magnetic alloy ribbon used in the cut core according to the present invention can be manufactured, for example, by spraying a molten alloy having a predetermined composition onto the surface of a cooling roll and rapidly solidifying it. The metal structure of the alloy ribbon obtained by this method may be amorphous, crystalline, or may be crystallized by heat treatment after rapid solidification. The thickness of the soft magnetic alloy ribbon is preferably 10 μm or more and 40 μm or less, since if it is 10 μm or more, the packing rate when made into a cut core is not significantly reduced, and if it is 40 μm or less, it is difficult to break when wound. A more preferable thickness of the soft magnetic alloy ribbon is 15 μm or more and 25 μm or less. The width of the soft magnetic alloy ribbon is not particularly limited because it varies greatly depending on the application of the cut core. For example, in the case of a cut core for a noise filter, the width of the soft magnetic alloy ribbon is preferably 5.0 mm or more and 50 mm or less.

[0025] The cut core according to the present invention includes two or more laminates in which soft magnetic alloy ribbons are laminated in the thickness direction. By laminating the soft magnetic alloy ribbons in the thickness direction, the cross-sectional area of ​​the magnetic path of the cut core can be increased, and the magnetic flux can be increased. The direction of the magnetic flux in the cut core coincides with the in-plane direction of the soft magnetic alloy ribbon. By forming the magnetic circuit of the cut core from two or more laminates, it is possible to separate at least one laminate from the magnetic circuit, or to reintegrate the separated laminate to reconstruct the magnetic circuit. This makes it possible to later arrange the cut core around a cable that has already been wired, or to later combine the cut core with a coil that has already been manufactured.

[0026] In the cut core according to the present invention, the laminate has at least one contact surface per laminate. The contact surface of the laminate is preferably arranged so as to be parallel to the thickness direction of the soft magnetic alloy ribbon constituting the laminate. In such a case, a cross section of the soft magnetic alloy ribbon cut at the contact surface is exposed at the contact surface. When the cut core is separated, the magnetic circuit is interrupted at the contact surface. When the cut core is reintegrated, the contact surfaces of the two or more laminates come into contact with each other, so that the entire cut core becomes an apparently continuous magnetic body, and the magnetic circuit that was once interrupted is reconstituted.

[0027] The laminate can be manufactured by bundling or winding soft magnetic alloy ribbons arranged in a predetermined shape into a roll. The ratio of the volume of the soft magnetic alloy ribbons to the total volume of the laminate, i.e., the packing rate, is preferably 65 vol% or more and 85 vol% or less, since the magnetic permeability does not decrease significantly if the packing rate is 65 vol% or more, and the residual strain does not increase if the packing rate is 85 vol% or less, and the impregnation with the adhesive described later is easy. The packing rate can be adjusted by the restraining force when bundling the soft magnetic alloy ribbons or the tension when winding them.

[0028] After producing the laminate, it is preferable to remove residual strain generated in the soft magnetic alloy ribbon by performing heat treatment before impregnating the laminate with an adhesive. The preferable heat treatment temperature is 350° C. or more and 700° C. or less. The heat treatment atmosphere is preferably an inert atmosphere such as nitrogen or argon, or a vacuum.

[0029] By impregnating the voids in the soft magnetic alloy ribbons constituting the heat-treated laminate with an adhesive, the soft magnetic alloy ribbons can be fixed and the shape of the laminate can be maintained. For the adhesive, organic adhesives such as acrylic resins, epoxy resins, polyimide resins, silicone resins, and silicone elastomers, and inorganic adhesives such as water glass, bentonite solvents, alumina solvents, and silica solvents can be used.

[0030] The viscosity of the adhesive is preferably, for example, 2000 mPa·s or less in order to make the adhesive permeate evenly into the gaps of the soft magnetic alloy ribbons. If the viscosity of the adhesive is higher than 2000 mPa·s, the adhesive can be made to permeate evenly into the gaps of the soft magnetic alloy ribbons by adjusting the viscosity by adjusting the temperature or adding a diluent such as an organic solvent, or by performing vacuum impregnation. Also, the adhesive may be applied to the surface before stacking the soft magnetic alloy ribbons.

[0031] When the adhesive used is a thermosetting resin, the adhesive is impregnated into the voids of the soft magnetic alloy ribbons, and then the entire laminate is heated to harden the adhesive. For example, in the case of an epoxy resin, the hardening temperature is preferably 50° C. or higher and 180° C. or lower.

[0032] Cut surfaces and discontinuous portions can be provided by cutting the laminate fixed by the adhesive. For example, a wet peripheral slicer equipped with a cutting wheel can be used for the cutting. For example, a GC wheel using a resinoid binder is suitable for the cutting wheel. The GC wheel used preferably has a bond degree of K-P, a grain size of 80-150, and a thickness in the range of about 0.5-1.5 mm.

[0033] The surface can be made smooth by polishing the cut surface or the surface of the discontinuous portion. In particular, when the cut surface or the surface of the discontinuous portion is used as the contact surface of the present invention, the arithmetic mean roughness Ra of the polished surface is preferably 0.70 μm or less, and the maximum height roughness Rz is preferably 10 μm or less. This allows the contact surfaces to be in close contact with each other, reducing gaps and preventing the flow of magnetic flux, thereby suppressing the decrease in magnetic permeability caused by forming the cut core. The arithmetic mean roughness Ra of the polished surface is more preferably 0.35 μm or less, and even more preferably 0.16 μm or less. The maximum height roughness Rz is more preferably 5.0 μm or less. The lower limits of the arithmetic mean roughness Ra and the maximum height roughness Rz are not particularly limited, but are within the range possible for mass production.

[0034] The flatness of the polished surface is preferably 2.5 μm or less. This allows the contact surfaces to be in close contact with each other, reducing gaps and preventing the flow of magnetic flux, thereby suppressing the decrease in magnetic permeability caused by forming the cut core. There is no particular lower limit for the flatness of the polished surface, but it should be within the range possible for mass production. When two or more contact surfaces are provided per laminate, it is preferable to appropriately adjust the angle between the two or more contact surfaces so that no gaps are generated at the contact surfaces when assembled into a cut core.

[0035] The area ratio of the cross section of the soft magnetic alloy ribbon exposed at the contact surface of the laminate formed by cutting and grinding depends on the packing ratio of the soft magnetic alloy ribbon in the laminate. For example, when the thickness of the soft magnetic alloy ribbon is 18 μm and the thickness of the adhesive layer is 4 to 5 μm on average, the area ratio of the cross section of the soft magnetic alloy ribbon at the contact surface is about 75 to 80%. In this case, the cross section of the soft magnetic alloy ribbon occupies most of the contact surface, so that magnetic continuity is always maintained even if the positions of two or more laminates in contact at the contact surface are shifted in a direction parallel to the contact surface.

[0036] In the cut core according to the present invention, the shape and size of the two contact surfaces of the two or more laminates that are in contact with each other are preferably the same, and the shapes of the two contact surfaces are preferably perfectly overlapped except for discontinuous parts, which reduces the magnetic flux leaking from the magnetic path and increases the magnetic permeability of the reconstructed magnetic circuit.

[0037] Even if the cut surface or the surface of the discontinuous portion produced by the cutting process is not used as the contact surface of the present invention, it is preferable to remove burrs produced on the cut surface or the surface of the discontinuous portion by polishing in order to improve the corrosion resistance of the surface. In this case, it is preferable to finish the polished surface to have the same level of arithmetic mean roughness Ra and maximum height roughness Rz as the contact surface.

[0038] [Component composition] The soft magnetic alloy ribbon used in the cut core according to the present invention is Fe100-x-y-z-a-b S x B y Cu z Cr a M b where M represents at least one element selected from Nb and Mo, and x, y, z, a, and b represent the atomic percentages of Si, B, Cu, Cr, and M, respectively, and satisfy 11.0≦x≦17.0, 5.0≦y≦10.0, 0.5≦z≦2.0, 0.5≦a≦4.0, 1.0≦b≦5.0, and 65≦100-xyzab≦75. The composition in this specification is expressed in atomic percentages unless otherwise specified.

[0039] Silicon, together with boron, is an element that promotes the amorphization of Fe-based alloys. The atomic percentage x of silicon is set to 11.0 or more and 17.0 or less, since amorphization is promoted when the atomic percentage x is 11.0 or more and magnetization is not significantly impaired when the atomic percentage x is 17.0 or less. Similarly, the atomic percentage y of boron is set to 5.0 or more and 10.0 or less, since amorphization is promoted when the atomic percentage x is 5.0 or more and magnetization is not significantly impaired when the atomic percentage y is 10.0 or less.

[0040] Cu is an element that tends to separate from Fe and forms nuclei during crystallization heat treatment to promote the refinement of crystals. If the atomic percentage z of Cu is 0.5 or more, the refinement of crystals is promoted, and if it is 2.0 or less, magnetization is not significantly impaired, so it is set to 0.5 or more and 2.0 or less.

[0041] Cr is an element that has the effect of increasing the corrosion resistance of the contact surface. If the atomic percentage a of Cr is 0.5 or more, the corrosion resistance of the contact surface increases, and if it is 4.0 or less, the magnetization is not significantly impaired, so it is set to 0.5 or more and 4.0 or less. From the viewpoint of improving the corrosion resistance, the atomic percentage a of Cr is preferably 2.5 or more.

[0042] The symbol M represents at least one element selected from Nb and Mo. The atomic percentage b of M represents the sum of the atomic percentages of Nb and Mo. Nb and Mo are elements that increase the crystallization temperature, suppress the grain growth of crystals, and promote refinement. If the atomic percentage b of M is 1.0 or more, refinement of crystals is promoted, and if it is 5.0 or less, magnetization is not significantly impaired, so it is set to 1.0 or more and 5.0 or less.

[0043] Fe is the main component that is the base of the soft magnetic alloy ribbon according to the present invention, and is the only element in the composition that is the source of ferromagnetism. In the above-mentioned notation of the composition, the atomic percentage of Fe is indicated by subtracting the total atomic percentage of elements other than Fe from 100. If the atomic percentage of Fe is 65 or more, the magnitude of magnetization is sufficient, and if it is 75 or less, the function of the added element is exerted without impairing the balance with other added elements, so it is set to 65 or more and 75 or less.

[0044] The cut core according to the present invention has the above-mentioned component composition, and therefore the corrosion resistance of the contact surface is improved compared to the cut core according to the prior art. This prevents rust from forming on the contact surface, so that the magnetic coupling due to the close contact on the contact surface is maintained even after long-term use, and the magnetic permeability of the magnetic circuit does not decrease.

[0045] [Intermediate diffusion layer and surface oxide layer] In a preferred embodiment, the cut core according to the present invention includes, at the contact surface, a substrate having the above-mentioned composition of the soft magnetic alloy ribbon, an intermediate diffusion layer located outside the substrate, in which Si is enriched and Fe is depleted compared to the composition of the soft magnetic alloy ribbon, and a surface oxide layer located outside the intermediate diffusion layer, which newly contains O (oxygen), is enriched in Si, and is depleted in Fe and Cr compared to the composition of the soft magnetic alloy ribbon. In this specification, the intermediate diffusion layer is "located outside the substrate" means that the intermediate diffusion layer is located on the surface of the substrate or on the side farther from the center of the substrate as viewed from the substrate. Similarly, in this specification, the surface oxide layer is "located outside the intermediate diffusion layer" means that the surface oxide layer is located on the surface of the intermediate diffusion layer or on the side farther from the center of the substrate as viewed from the intermediate diffusion layer located outside the substrate.

[0046] The intermediate diffusion layer and the surface oxide layer will be described below using actual data. FIG. 1 is a graph showing the relationship between the distance from the surface and the ratio of elements in the contact surface exposed by removing the products produced during ribbon production by polishing the surface of the side not in contact with the cooling roll of the soft magnetic alloy ribbon of the invention example 3 shown in the embodiment 1 described later without performing heat treatment for crystallization with abrasive paper of No. 600. The ratio of elements was measured by glow discharge optical emission spectroscopy (GD-OES). The composition of the soft magnetic alloy ribbon of the invention example 3 was Fe: 69.5%, Si: 15.5%, B: 7.0%, Cu: 1.0%, Cr: 4.0%, and Nb: 3.0%. The horizontal axis of FIG. 1 is the distance (nm) from the surface, and the vertical axis is the ratio of elements at each distance (at%). FIG. 1 shows the ratios of Fe, Si, Cr, and O (oxygen) among the measured ratios of elements. Of these, for Fe, the analytical value is multiplied by 1 / 2 (Fe / 2) and displayed.

[0047] According to FIG. 1, in the region indicated by symbol C at a distance of 50 nm or more from the surface of the soft magnetic alloy ribbon of Example 3, the ratio of elements shows an almost constant value. This region C corresponds to the substrate having the above-mentioned composition. The region indicated by symbol B at a distance of 8 nm or more and 50 nm or less from the surface is located outside the substrate, and the ratio of Si increases gradually and the ratio of Fe decreases gradually as it approaches the surface. This region B corresponds to an intermediate diffusion layer in which Si is concentrated and Fe is depleted compared to the composition of the soft magnetic alloy ribbon. The region indicated by symbol A at a distance of 0 nm or more and 8 nm or less from the surface is located outside the intermediate diffusion layer, and the ratios of Si and O are extremely high and the ratios of Fe and Cr are decreased compared to the substrate. This region A corresponds to a surface oxide layer which newly contains O (oxygen), is concentrated in Si, and is depleted in Fe and Cr compared to the composition of the soft magnetic alloy ribbon.

[0048] In the graph showing the change in the ratio of elements exemplified in FIG. 1, the method of determining the position of the boundary between the substrate (region C) and the intermediate diffusion layer (region B) and the position of the boundary between the intermediate diffusion layer (region B) and the surface oxide layer (region A) is not particularly limited. For example, the point on the graph where the ratio value of the elements changes from the region of the substrate, which is constant and has the same value as the composition of the soft magnetic alloy ribbon, to an increase or decrease can be determined as the boundary between the substrate and the intermediate diffusion layer. In addition, for example, the point where the second derivative coefficient of the ratio value of the elements with respect to the distance from the surface changes significantly can be determined as the boundary between the intermediate diffusion layer and the surface oxide layer. If it is not possible to clearly determine these points for all elements, these points may be determined using the ratio of at least one element among the ratios of elements shown in the graph.

[0049] In this preferred embodiment, the mechanism by which the surface oxide layer and the intermediate diffusion layer are formed on the contact surface is not clearly understood, but the following is probably possible. As described above, the contact surface is formed by processing the laminate in which the soft magnetic alloy ribbons are laminated, by cutting, polishing, etching, etc. For example, when processing is performed by wet polishing, the contact surface formed during the polishing process comes into contact with water and other media used for polishing and cleaning. In addition, when drying the polished surface after cleaning, the contact surface comes into contact with heated air. It is considered that the oxide of Si is generated by O taken into the surface of the contact surface during these processes, and as a result, a surface oxide layer containing O, concentrated Si, and deficient in Fe and Cr is formed. The O contained in the surface oxide layer is not contained in the substrate, and is taken into the soft magnetic alloy ribbon after the contact surface is formed. On the other hand, it is considered that the intermediate diffusion layer is formed as a result of Si and O diffusing with the concentration difference between Si and O in the substrate and the surface oxide layer as a driving force.

[0050] In addition, although the mechanism by which rusting of the contact surface is prevented in this preferred embodiment is not clearly understood, it is believed that the corrosion resistance of the contact surface is improved and rusting is prevented by the presence of an intermediate diffusion layer (region B) outside the base material (region C) and a surface oxide layer (region A) outside that. Note that, since the surface oxide layer and intermediate diffusion layer are deficient in Cr compared to the base material, the above-mentioned rust prevention effect is believed to be due to a mechanism different from the rust prevention by the formation of a passive film, which is generally known for Fe-Cr alloys.

[0051] Regarding the cut core according to the present invention, the processing form for forming the contact surface of the laminate may be any form of processing as long as the base material is exposed. As described above, the processing of the laminate can be performed by cutting, polishing, etching, etc., but the processing method is not limited to these.

[0052] [Fe-based nanocrystalline alloy] In a preferred embodiment, in the cut core according to the present invention, the soft magnetic alloy ribbon contains an Fe-based nanocrystalline alloy.

[0053] The Fe-based nanocrystalline alloy is a soft magnetic alloy that can be obtained by spraying a molten alloy containing Fe as the main component onto the surface of a cooling roll, rapidly solidifying the quenched ribbon, and then heat-treating the quenched ribbon. The quenched ribbon before heat-treating is in an amorphous state due to the action of Si and B contained in the composition at the above-mentioned predetermined ratio. By heat-treating the quenched ribbon, fine crystals with a crystal grain size of more than 0 nm and not more than 60 nm are crystallized in the amorphous base. This results in a soft magnetic alloy ribbon with a uniform grain size, fine crystal structure, and excellent soft magnetic properties. In addition, in the Fe-based nanocrystalline alloy, there remains a portion that has not crystallized and remains in an amorphous state even after heat-treating.

[0054] The heat treatment temperature for crystallizing the quenched ribbon is preferably 350° C. to 700° C. The heat treatment is preferably performed in an inert atmosphere such as nitrogen or argon, or in a vacuum.

[0055] The heat treatment of the quenched ribbon is preferably carried out after the quenched ribbon is laminated. This is because the soft magnetic alloy ribbon after the heat treatment of the quenched ribbon is brittle and easily cracked, making it difficult to handle. By laminating the quenched ribbon in advance to form a laminate and then carrying out the heat treatment, damage to the laminate due to cracking of the soft magnetic alloy ribbon can be prevented. By carrying out the heat treatment for crystallization, the residual strain introduced during the manufacture of the quenched ribbon and the assembly of the laminate can be simultaneously removed. When carrying out the heat treatment after laminating the quenched ribbon, it is preferable to fix the laminate using a jig or the like so that it does not separate into the original quenched ribbon.

[0056] As in the case of a soft magnetic alloy ribbon that is not subjected to heat treatment for crystallization, even when the soft magnetic alloy ribbon contains an Fe-based nanocrystalline alloy, it is preferable from the standpoint of corrosion resistance that the soft magnetic alloy ribbon at the contact surface has a base material, an intermediate diffusion layer located outside the base material, and a surface oxidation layer located outside the intermediate diffusion layer.

[0057] The intermediate diffusion layer and the surface oxide layer in the case where the soft magnetic alloy ribbon contains an Fe-based nanocrystalline alloy will be described below using actual data. FIG. 2 is a graph showing the relationship between the distance from the surface and the ratio of elements in the contact surface of a soft magnetic alloy ribbon containing an Fe-based nanocrystalline alloy, which is crystallized by heat treatment at 550° C. for 90 minutes in an argon atmosphere for the soft magnetic alloy ribbon of Example 3 of the invention shown in Example 2 described later. As in the case of FIG. 1, the ratio of elements was measured by glow discharge optical emission spectroscopy (GD-OES). As in the case of FIG. 1, the soft magnetic alloy ribbon containing an Fe-based nanocrystalline alloy shown in FIG. 2 also has a region C corresponding to the substrate, a region B corresponding to the intermediate diffusion layer, and a region A corresponding to the surface oxide layer. The boundary between the substrate and the intermediate diffusion layer is not very clear, but seems to be located near a position 50 nm away from the surface. The boundary between the intermediate diffusion layer and the surface oxide layer is located at a position 8 nm away from the surface, as in the case of FIG. 1. The ratio of O at the outermost surface is higher than that in FIG. 1, and conversely, the ratio of Si is lower than that in FIG. 1.

[0058] [Oxygen concentration at the outermost surface of the surface oxide layer] In a preferred embodiment, the cut core according to the present invention has a soft magnetic alloy ribbon containing an Fe-based nanocrystalline alloy, and the oxygen concentration at the outermost surface of the surface oxide layer is 43.0 atomic % or more. When the oxygen concentration at the outermost surface of the surface oxide layer is 43.0 atomic % or more, the corrosion resistance of the contact surface of the laminate is particularly excellent. Although there is no particular upper limit for the oxygen concentration at the outermost surface of the surface oxide layer, it is preferably 60.0 atomic % or less.

[0059] There is no particular limitation on the method for increasing the oxygen concentration at the outermost surface of the surface oxide layer to 43.0% or more. For example, in the case of a soft magnetic plywood ribbon containing an Fe-based nanocrystalline alloy having the component composition specified in the present invention and obtained by heat treatment for crystallization, the oxygen concentration at the outermost surface of the surface oxide layer can be increased to 43.0% or more by carrying out a heating treatment in which the laminate having the contact surface formed after the heat treatment is held in the air at 130°C for 8 hours. The temperature of this heating treatment is lower than the heat resistance temperature of the adhesive that fixes the laminate.

[0060] As shown in FIG. 2, in the case of a soft magnetic plywood strip containing an Fe-based nanocrystalline alloy that has been subjected to heat treatment for crystallization, the oxygen concentration at the outermost surface of the surface oxidation layer immediately after the contact surface is formed is less than 40.0 atomic %, and it is difficult to increase the oxygen concentration to 43.0% or more. In addition, in the case of a soft magnetic plywood strip containing an Fe-based nanocrystalline alloy immediately after heat treatment in an argon atmosphere for crystallization and before the contact surface is formed, the oxygen concentration at the outermost surface of the surface oxidation layer is about 37.0 atomic %, and it is also difficult to increase the oxygen concentration to 43.0% or more. Therefore, in order to increase the oxygen concentration at the outermost surface of the surface oxidation layer to 43.0% or more, it is preferable to perform a heating treatment in which the laminate with the contact surface formed after the heat treatment is held in the air at 130° C. for 8 hours for the soft magnetic plywood strip containing an Fe-based nanocrystalline alloy obtained by heat treatment for crystallization.

[0061] If the temperature of the heat treatment in the atmosphere is too low, the oxygen concentration at the outermost surface of the surface oxide layer cannot be 43.0 atomic % or more. Therefore, the heat treatment temperature is preferably 100°C or more, more preferably 120°C or more. On the other hand, if the temperature of the heat treatment is too high, the oxygen concentration at the outermost surface of the surface oxide layer exceeds 60.0 atomic %. Therefore, the heat treatment temperature is preferably 160°C or less, more preferably 140°C or less. The preferable treatment time of the heat treatment is a time required for the oxygen concentration at the outermost surface of the surface oxide layer to be 43.0 atomic % or more in the above-mentioned preferable temperature range, taking into account the heat capacity of the laminate and other conditions.

[0062] FIG. 3 is a graph showing the relationship between the distance from the surface at the contact surface and the ratio of elements in a soft magnetic alloy ribbon including an Fe-based nanocrystalline alloy, which is crystallized by heat treatment at 550° C. for 90 minutes in an argon atmosphere for the soft magnetic alloy ribbon of Example 14 shown in Example 2 described later, and further heat treatment is performed by holding the ribbon in air at 130° C. for 8 hours. The composition of the soft magnetic alloy ribbon of Example 14 is the same as that of the soft magnetic alloy ribbon of Example 3 shown in FIGS. 1 and 2. As in the cases of FIGS. 1 and 2, the ratio of elements was measured by glow discharge optical emission spectroscopy (GD-OES). The ratio of elements in the intermediate diffusion layer of this sample is not significantly different from that of the intermediate diffusion layer shown in FIG. 2. On the other hand, in the surface oxide layer of FIG. 3, the oxygen concentration at the outermost surface reaches 44.6 atomic %, and conversely, the concentration of Si at the outermost surface is lower than that in FIG. 2. In addition, the boundary between the intermediate diffusion layer and the surface oxide layer is located at a distance of 10 nm from the surface, and the thickness of the surface oxide layer is slightly increased compared to Figures 1 and 2. As shown in Example 3 described later, in Example 14 of the invention, in which the oxygen concentration at the outermost surface of the surface oxide layer is 43.0 atomic % or more, the corrosion resistance of the contact surface of the laminate was particularly superior to that of Comparative Example 2, in which the oxygen concentration was 42.6 atomic %.

[0063] [Impedance change rate] In a preferred embodiment, the cut core according to the present invention is a cut core in which the soft magnetic alloy ribbon contains an Fe-based nanocrystalline alloy, and the impedance at a frequency of 100 kHz is measured before and after immersion of the cut core in ion-exchanged water for 100 hours, and the measured value before immersion is expressed as Z A , the measured value after immersion is Z B Then, (Z B -Z A ) / Z AThe absolute value of the impedance change rate ΔZ calculated by multiplying the impedance change rate ΔZ by 100 is 15% or less. Generally, when a cut core is immersed in ion-exchanged water, red rust is generated on the contact surface. As a result, the impedance after immersion is lower than the impedance before immersion. In this case, the impedance change rate ΔZ is a negative value, and the larger the absolute value of ΔZ, the greater the degree of rusting. In the cut core according to the present invention, the corrosion resistance of the contact surface is improved due to the presence of the surface oxide layer and the intermediate diffusion layer, so that the absolute value of the impedance change rate ΔZ under the above evaluation conditions does not exceed 15%. More preferably, the absolute value of the impedance change rate ΔZ is 12% or less.

[0064] The temperature of the ion-exchanged water when the cut core is immersed is not particularly limited, but the temperature of the ion-exchanged water is preferably room temperature. Room temperature is, for example, 25° C. In addition, the temperature when the impedance of the cut core is measured is not particularly limited, but the temperature of the cut core and the surrounding environment is preferably room temperature.

[0065] [Cut core with contact cutting surface] In a preferred embodiment, the cut core according to the present invention comprises n laminates formed by cutting an annular body formed by winding a soft magnetic alloy ribbon into an annular shape at n locations (n ​​is an integer of 2 or more) perpendicularly to the circumferential direction of the annular body, with (n×2) cut surfaces of the n laminates serving as contact surfaces, and two adjacent laminates among the n laminates contact each other at the cut surfaces serving as contact surfaces to form a magnetic circuit as a whole. Fig. 4 is a schematic diagram showing an example of the shape of the cut core according to this preferred embodiment.

[0066] The cut core 1 illustrated in Fig. 4 includes two laminates 2 obtained by dividing one annular body formed by winding a soft magnetic alloy ribbon into two equal parts. Each laminate 2 includes two cut surfaces perpendicular to the circumferential direction. The soft magnetic alloy ribbon can be wound by winding a long soft magnetic alloy ribbon in multiple layers around the outer circumferential surface of a jig having a cylindrical shape, for example, while applying tension to the long soft magnetic alloy ribbon.

[0067] The shape of the cut core before cutting may be any shape as long as it is closed in an annular shape, and may be any shape such as a circle, the shape of an athletics track, a rectangle with rounded corners, etc. However, since there is a limit to the deformability in bending a soft magnetic alloy ribbon, the radius of curvature of the curved surface needs to be equal to or larger than the limit.

[0068] As shown in FIG. 4, the cut surface can be provided, for example, perpendicular to the circumferential direction of the soft magnetic alloy ribbon. In this specification, the "circumferential direction" refers to the direction in which the soft magnetic alloy ribbon is wound. More strictly, it refers to the direction of the tangent of the soft magnetic alloy ribbon at the position where the soft magnetic alloy ribbon contacts the outermost surface of the already wound laminate. By using the cut surface perpendicular to the circumferential direction as the contact surface, the area of ​​the contact surface can be reduced. In addition, the contact surface being perpendicular to the circumferential direction is also convenient when applying a force perpendicular to the contact surface to bring them into close contact. However, the direction of the cut surface does not necessarily have to be perpendicular to the circumferential direction and can be provided in any direction.

[0069] Two or more laminates 2 come into contact with each other at the contact surface 2a, and together form a magnetic circuit. The magnetic circuit is reconstructed by closing the magnetic path formed by the continuous laminates in a ring shape. In FIG. 4, the number of laminates 2 constituting the cut core 1 is two, but the number of laminates 2 may be three or more. In FIG. 4, the two laminates 2 constituting the cut core 1 have the same size, but the magnetic path of one of the two laminates 2 may be longer and the magnetic path of the other may be shorter.

[0070] [End contact type cut core] In a preferred embodiment, the cut core according to the present invention includes two or more laminates formed by providing a discontinuous portion at a circumferential portion of an annular body formed by winding a soft magnetic alloy ribbon in an annular shape, at least one of two widthwise end faces of each of the two or more laminates serves as a contact surface, and two adjacent laminates among the two or more laminates contact each other at the widthwise end face as a contact surface such that the discontinuous portions do not overlap in the circumferential direction, thereby forming a magnetic circuit as a whole. Fig. 5 is a schematic diagram showing an example of the shape of the cut core according to this preferred embodiment.

[0071] In the cut core 1 illustrated in FIG. 5, each laminate 2 has one discontinuous portion 2b. In this specification, the term "discontinuous portion" refers to a portion where the continuity in the winding direction of the soft magnetic alloy ribbon wound in an annular shape is broken due to a lack of a part of the annular body. The width of the discontinuous portion 2b may be large enough to allow a cable or the like to pass through. The magnetic path of one laminate 2 is interrupted at the discontinuous portion 2b. By providing the discontinuous portion 2b in the laminate 2, when the two laminates 2 are separated, for example, a cable can be moved from the outside to the inside of the annular laminate through the discontinuous portion 2b.

[0072] In this preferred embodiment, the discontinuous portion 2b can be provided in the laminate 2 by, for example, impregnating a soft magnetic alloy wound in an annular shape with an adhesive, fixing the soft magnetic alloy, and then cutting the soft magnetic alloy to remove a part of the laminate 2. Alternatively, flat soft magnetic alloy ribbons cut in advance to a predetermined shape can be laminated, and the whole laminate can be bent to form the annular shape having the discontinuous portion 2b.

[0073] In this preferred embodiment, the discontinuous portion 2b is not a contact surface. The pair of cross sections constituting the discontinuous portion 2b does not need to be perpendicular to the winding direction of the soft magnetic alloy ribbon, and may have any angle with respect to the winding direction. However, it is preferable that the pair of cross sections constituting the discontinuous portion 2b are parallel to each other from the viewpoint of ease of movement of the cable.

[0074] At least one of the two widthwise end faces of each laminate 2 is a contact surface 2a, and the laminates 2 contact each other at the contact surface 2a so that the discontinuous parts 2b do not overlap, thereby forming a magnetic circuit as a whole. The "widthwise end faces" of the laminate 2 refer to the two end faces perpendicular to the central axis 2c of the winding in the laminate 2 obtained by winding the soft magnetic alloy ribbon in a ring shape. As a result of winding the soft magnetic alloy ribbon, the ends of the soft magnetic alloy ribbon in the width direction are stacked on each other at the end faces of the laminate. By bringing two or more laminates 2 into contact with each other at the contact surface 2a so that the discontinuous parts 2b do not overlap, the magnetic path interrupted by the discontinuous parts 2b in one laminate 2 is connected by the other laminate 2 adjacent to it, so that a closed magnetic circuit is reconstructed as a whole. As described above, it is preferable to smooth the contact surface 2a by polishing the contact surface 2a. It is not necessary for the contact surface 2a to be strictly perpendicular to the central axis 2c of the winding, but it may have a slight angle with respect to the winding direction.

[0075] In FIG. 5, the number of laminates 2 constituting the cut core 1 is two, but the number of laminates 2 may be three or more. In FIG. 5, the size of the two laminates 2 constituting the cut core 1 is the same, but one of the two laminates 2 may be thicker and the other may be thinner. When the number of laminates 2 is three or more, the laminate 2 located in the middle has both widthwise end faces perpendicular to the central axis of winding as contact surfaces 2a. In addition, when the number of laminates 2 is three or more, it is sufficient that the discontinuous parts 2b do not overlap between two laminates 2 that are in contact with each other and adjacent to each other, and the discontinuous parts 2b may overlap between laminates 2 located at distant positions.

[0076] [case] The cut core can be used by being housed in a case (not shown). In this case, it is preferable to house one laminate 2 in one case so that all the contact surfaces 2a of the laminate 2 are exposed from the case. This allows the magnetic circuit to be reconstructed by fitting the cases together to bring the contact surfaces 2a of the laminate 2 into contact. The case can be made of materials such as PBT (polybutylene terephthalate), PA (polyamide), PPS (polyphenylene sulfide), ABS (acrylonitrile butadiene styrene), ASA (acrylonitrile styrene acrylic rubber), silicone resin, silicone elastomer, etc.

[0077] The case preferably includes a load mechanism that can press the opposing contact surfaces 2a tightly together by fitting them together. The load mechanism may have any structure as long as it can maintain tight contact between the contact surfaces 2a. The load mechanism that the case includes may be, for example, a leaf spring, a protrusion, or a band made of resin or metal.

[0078] If the load applied to the contact surface 2a by the load mechanism of the case is 5 times or more the mass of the laminate 2, it is possible to prevent the contact surface 2a from coming off due to vibration or impact when the cut core 1 is in use. If the load is 100 times or less the mass of the laminate 2, it is possible to prevent the soft magnetic properties from being impaired due to distortion caused by deformation of the laminate 2. Therefore, it is preferable that the load applied to the contact surface 2a is 5 times or more and 100 times or less the mass of the laminate 2. The means for applying a load to the contact surface 2a does not necessarily have to be the fitting of the case, and may be a simple means such as fastening two or more laminates 2 with vinyl tape or a cable tie.

[0079] [Noise suppression materials] In another embodiment, the present invention relates to a noise countermeasure member. The noise countermeasure member according to the present invention is a noise countermeasure member using the cut core according to the present invention. As described above, the cut core 1 according to the present invention can be separated or integrated at the contact surface 2a. When the cut core 1 is separated into two or more laminated bodies 2, the laminated bodies 2 can be disposed later at any position on, for example, an already-wired cable. Thereafter, by integrating the laminated bodies 2, the magnetic circuit that was interrupted by the separation can be easily reconstructed.

[0080] As described above, the cut core 1 according to the present invention has excellent corrosion resistance at the contact surface 2a, and therefore can maintain its noise reducing performance for a long period of time even after being installed around cables, etc. as a noise countermeasure member. Therefore, the noise countermeasure member according to the present invention can be suitably used, for example, in electrical equipment or electronic devices in which the noise countermeasure member cannot be easily replaced after installation. EXAMPLES

[0081] The present invention will be described below with reference to examples, but the present invention is not limited to these.

[0082] [Example 1] (Evaluation of alloy ribbon) The alloy melts having the composition of the invention examples 1-11 and the comparative example 1 shown in Table 1 were quenched by a single roll method to obtain alloy strips made of Fe-based amorphous alloys having a width of 10 mm and a thickness of 23 μm. The obtained alloy strips were cut to a length of 15 mm, and the surface on the side not in contact with the cooling roll, i.e., the free surface, was polished with abrasive paper of No. 600 to remove the products produced during the strip production, to obtain test pieces simulating the contact surface exposed by processing. In addition to these test pieces, test pieces having the composition of the invention examples 12-22 and the comparative example 2 shown in Table 1 were also prepared by the same process, and test pieces were prepared by exposing the contact surface and then heating the test pieces at 130° C. in air for 8 hours.

[0083] Next, all the test pieces obtained were immersed in ion-exchanged water at 25°C for 24 hours, and the polished surfaces of the test pieces after immersion were visually observed to evaluate the corrosion resistance based on the presence or absence of discoloration and rust. The evaluation results were as follows: no discoloration at all was rated "excellent," whitish discoloration but no red rust was rated "good," red rust was rated on 20% or less of the entire observation surface was rated "passing," and red rust was rated on more than 20% of the entire observation surface was rated "failing." The evaluation results are shown in Table 1.

[0084] [Table 1]

[0085] According to the evaluation results of corrosion resistance shown in Table 1, in the polished surface simulating the contact surface of the cut core according to the present invention, the specimens of the invention examples 1 to 11, in which the Cr content is 0.5 or more and 4.0 or less in atomic percentage, showed less rusting than the specimen of the comparative example 1, which does not contain Cr. In particular, when the Cr content is 2.5 or more in atomic percentage, the evaluation result was "good" or "excellent", and red rusting did not occur. Moreover, the specimens of the invention examples 12 to 22, in which the Cr content is 0.5 or more and 4.0 or less in atomic percentage and which were subjected to heating treatment at 130°C for 8 hours in air after polishing, showed no discoloration or rusting, unlike the specimen of the comparative example 2, which does not contain Cr, in which red rusting was observed.

[0086] [Example 2] (Oxygen concentration at the outermost surface of the surface oxide layer) The alloy ribbons having the composition of the invention examples 1-3 and comparative example 1 shown in Table 1 were produced by the same process as in Example 1, and were heat-treated at 550°C for 90 minutes in an argon atmosphere to crystallize, to obtain soft magnetic alloy ribbons containing Fe-based nanocrystalline alloys. The obtained alloy ribbons were cut to a length of 15 mm, and the surface on the side not in contact with the cooling roll, i.e., the free surface, was polished with abrasive paper of No. 600 to remove the products produced during the ribbon production, to obtain test pieces simulating the contact surface exposed by processing. In addition to these test pieces, test pieces having the composition of the invention examples 12-14 and comparative example 2 shown in Table 1 were produced by the same process, and test pieces were also prepared by exposing the contact surface and then heating the exposed surface in air at 130°C for 8 hours.

[0087] Next, the oxygen concentration on the polished outermost surface of each test piece was measured by glow discharge optical emission spectroscopy (GD-OES). The measurement was performed using a GD-Profiler2 manufactured by Horiba, Ltd. The measurement results are shown in Table 2.

[0088] [Table 2]

[0089] According to the measurement results shown in Table 2, in the soft magnetic plywood ribbon containing the Fe-based nanocrystalline alloy that was subjected to heat treatment for crystallization, the oxygen concentration at the outermost surface of the surface oxide layer in the test piece immediately after the contact surface was exposed was 39.5 atomic % or less. On the other hand, in the test piece in which the contact surface was exposed and then heat treatment was performed in air at 130°C for 8 hours, the oxygen concentration at the outermost surface of the surface oxide layer was 43.0 atomic % or more, except for Comparative Example 2. In contrast, the oxygen concentration at the outermost surface of the surface oxide layer in the test piece of Comparative Example 2 was 42.6 atomic %.

[0090] [Example 3] (Evaluation of magnetic core) In the same manner as in Example 1, the alloy melt having the composition shown in Table 1 was quenched by a single roll method to obtain an alloy strip made of an Fe-based amorphous alloy having a width of 10 mm and a thickness of 23 μm. The obtained alloy strip was wound to form a cylindrical laminate having an outer diameter of 28.5 mm, an inner diameter of 18.0 mm, and a height of 10 mm. However, the laminate according to this example did not have the discontinuous portion 2b shown in FIG. 4, and the entire laminate was continuous without any seams. Next, the cylindrical laminate made of an Fe-based amorphous alloy was heat-treated at 550° C. for 90 minutes in an argon atmosphere to crystallize it, and a magnetic core made of an Fe-based nanocrystalline alloy was produced.

[0091] Next, the obtained magnetic core was immersed in a solution of Mitsubishi Chemical's epoxy resin 801N and hardener ST12 mixed in a specified ratio, evacuated to -0.1 MPaG, and held for 10 minutes, then released to atmospheric pressure to impregnate the magnetic core with the epoxy resin. The magnetic core impregnated with the epoxy resin was left at room temperature for 24 hours, and then held in air at 80°C for 3 hours to harden the epoxy resin and fix the Fe-based nanocrystalline alloy ribbon.

[0092] Next, the end face perpendicular to the central axis of the winding of the magnetic core, that is, the plane parallel to the thickness direction of the soft magnetic alloy ribbon, was polished. The polished plane of the magnetic core corresponds to the contact surface 2a in the end face contact type cut core 1 shown in FIG. 5. A Tegramin-25 manufactured by Struers was used for polishing the plane. The polishing conditions were a revolution of 100 rpm, a rotation of 50 rpm, and rotation in the same direction, and a load of 15 N. The grit of the abrasive paper was gradually reduced from 220 to 320, 500, 800, 1200, and 2000, and magnetic cores (Invention Examples 1-11 and Comparative Example 1) were prepared by polishing the plane on one side. In addition, magnetic cores (Invention Examples 12-22 and Comparative Example 2) were also prepared by heating the obtained magnetic cores at 130°C in air for 8 hours. The coercive force of the obtained magnetic cores was measured using an automatic coercive force meter K-HC1000 manufactured by Tokyo Tokushu Kogyo Co., Ltd. For each magnetic core, the magnetic core was immersed in water and the polished flat surface was subjected to an evaluation of corrosion resistance in the same manner as in Example 1. The obtained results are shown in Table 3.

[0093] [Table 3]

[0094] According to the evaluation results shown in Table 3, the magnetic cores exhibited good soft magnetic properties, with the coercive force being lower than 15.0 A / m, except for Examples 6 and 17. As for corrosion resistance, similar to the evaluation results of Example 1, the magnetic cores of Examples 1 to 11, which contain Cr in their composition, exhibited good corrosion resistance, and the magnetic cores of Examples 12 to 22, which were subjected to heat treatment, exhibited particularly excellent corrosion resistance.

[0095] The results of Example 2 shown in Table 2 and the results of Example 3 shown in Table 3 show the following. According to Table 3, in the magnetic cores of Examples 12 to 22 of the invention, which were subjected to the heating treatment, no discoloration was observed on the surface of the test piece simulating the contact surface, and the magnetic cores showed particularly excellent corrosion resistance. According to Table 2, in the soft magnetic plywood strips containing the Fe-based nanocrystalline alloy of Examples 12 to 22 constituting these magnetic cores, the oxygen concentration at the outermost surface of the surface oxidation layer was 43.0 atomic % or more. On the other hand, according to Table 3, in the magnetic core of Comparative Example 2, which was also subjected to the heating treatment, red rust occurred over an area of ​​more than 20% of the surface of the test piece. According to Table 2, in the soft magnetic plywood strip containing the Fe-based nanocrystalline alloy of Comparative Example 2 constituting this magnetic core, the oxygen concentration at the outermost surface of the surface oxidation layer was 42.6 atomic %, which is lower than 43.0 atomic %. These results show that in a soft magnetic plywood ribbon containing an Fe-based nanocrystalline alloy, when the oxygen concentration at the outermost surface of the surface oxide layer formed on the contact surface is 43.0 atomic % or more, the contact surface exhibits particularly excellent corrosion resistance.

[0096] [Example 4] (Effect of surface roughness) In the same manner as in Example 2, a Fe-based nanocrystalline alloy ribbon having the component composition shown in Table 1 was wound to form a laminate, and then a magnetic core was produced by impregnating and fixing the laminate with epoxy resin, and the end faces perpendicular to the central axis of the winding of the obtained magnetic core were polished. In the flat surface polishing process, the polishing process was stopped at each stage of the grit size of the abrasive paper of 220, 320, 800, and 2000. Next, a part of the obtained magnetic core was subjected to a heating process at 130°C in air for 8 hours. The arithmetic average roughness Ra of the polished surface was measured using a laser microscope VK-X3000 manufactured by Keyence. The measurement magnification was 480 times, the objective lens magnification was 20 times, the cutoff wavelength was set to S-filter 2.75 μm, and the L-filter was set to 0.8 mm, and one line was measured from the inner circumference side to both end faces from the outer circumference side. For each test piece, the magnetic core was immersed in water, and the corrosion resistance was evaluated for the polished flat surface in the same manner as in Example 1. The results are shown in Table 4.

[0097] [Table 4]

[0098] According to the evaluation results shown in Table 4, in the polished surface simulating the contact surface of the cut core according to the present invention, the arithmetic mean roughness Ra of the polished surface decreased with increasing grit size of the abrasive paper used for polishing in all samples. In addition, in the sample pieces of invention examples 1 to 11, in which the Cr content is 0.5 or more and 4.0 or less in atomic percentage, the corrosion resistance tended to improve with decreasing arithmetic mean roughness Ra of the polished surface. In particular, in the case of the abrasive paper with a grit size of 2000, the area of ​​the part where red rust occurred was 20% or less of the entire observation surface (excellent, good or fair) in all samples. Furthermore, in the samples of invention examples 12 to 22, which were subjected to heating treatment after polishing, no discoloration or rusting was observed at all (excellent). In contrast, in the samples of comparative examples 1 and 2, which do not contain Cr, the area of ​​the part where red rust occurred exceeded 20% of the entire observation surface for all grit sizes of the abrasive paper (unacceptable).

[0099] [Example 5] (Evaluation of cut core) In the same manner as in Example 3, an Fe-based nanocrystalline alloy ribbon having the component composition shown in Table 1 was impregnated with epoxy resin, wound to form a laminate, and then impregnated with epoxy resin to produce a magnetic core. Next, the obtained magnetic core was cut so that the shape of the laminate became the shape shown in FIG. 5, and a discontinuous portion was provided. Cutting was performed manually using a high-speed precision cutting machine Finecut HS-100 manufactured by Heiwa Technica Co., Ltd., and a grindstone Tokusutoshisten B (outer diameter φ205 mm, inner diameter φ25.4 mm, thickness 0.7 mm) manufactured by Heiwa Technica Co., Ltd., to provide a discontinuous portion with a width of 10 mm.

[0100] Next, in the same manner as in Example 3, one end face perpendicular to the central axis of the winding of the magnetic core having discontinuous parts was polished using up to No. 2000 abrasive paper. Then, heating treatment was performed in air at 130°C for 8 hours. The surface roughness of the polished surface was Ra 0.1 μm and Rz 1.0 μm. Using two of the obtained polished magnetic cores, the polished end faces were brought into contact with each other so that the angle formed by the center positions of the discontinuous parts was 180° as shown in FIG. 5, and fixed with heat-resistant tape to form a cut core. The coercive force of the obtained cut core was measured in the same manner as in Example 3.

[0101] Next, in the same manner as in Example 1, the cut core was immersed in ion-exchanged water at 25° C. for 100 hours, and the impedance at a frequency of 100 kHz was measured before and after immersion. The measured value before immersion was Z A , the measured value after immersion is Z B Then, (Z B -Z A ) / Z A The impedance change rate ΔZ (%) was calculated by multiplying the impedance by ΔZ by 100. A Keysight impedance analyzer 4294A was used to measure the impedance. The temperature of the cut core and the surrounding environment when measuring the impedance was 25°C. One turn of a lead wire H-PVC, Φ0.5mm single wire, manufactured by Tanaka Electric Wire, was passed through the cut core, and the cut core was fixed using a Keysight lead wire fixing jig 16047E for measurement. At this time, a weight with a mass of 100g was placed on the cut core to apply a load to the contact surface and bring them into close contact.

[0102] Next, a cut core other than the one used for the water immersion was held for 1000 hours in an environment of 85°C and 85% RH using an Espec SH-222 small environmental tester, and the rate of change in impedance at a frequency of 100 kHz, ΔZ, was calculated before and after the test in the same manner as for the water immersion. The evaluation results are shown in Table 5.

[0103] [Table 5]

[0104] According to the evaluation results shown in Table 5, in both test conditions of water immersion and 85°C, 85% RH, the absolute value of the impedance change rate ΔZ in the cut cores of Examples 12 to 22 according to the present invention was smaller than that of Comparative Example 2 and did not exceed 15%. In the cut core according to Comparative Example 2, it is considered that the occurrence of red rust on the contact surface impairs the adhesion of the contact surface as in the case of Example 2, and as a result, the magnetic permeability decreases, and as a result, the absolute value of the impedance change rate ΔZ becomes larger. In contrast, in the cut core according to the present invention, it is considered that the occurrence of red rust on the contact surface is suppressed compared to Comparative Example 2, and as a result, the absolute value of the impedance change rate ΔZ is smaller than that of Comparative Example 2. [Industrial Applicability]

[0105] This cut core is attached to the power cables of electronic devices such as automobiles, power generation and power supply facilities, communication devices, and OA / FA devices, and can be used as a noise suppression core to suppress noise generated inside these electronic devices or noise generated externally and propagating inside the cable. [Explanation of symbols]

[0106] A Surface oxide layer B Intermediate diffusion layer C Base material 1 Cut Core 2. Laminate 2a Contact surface 2b Discontinuity 2c Central axis of winding

Claims

1. A cut core having two or more laminates in which soft magnetic alloy ribbons are laminated in a thickness direction, The laminates each have at least one contact surface, and are in contact with each other at the contact surfaces; The soft magnetic alloy ribbon is Fe 100-x-y-z-a-b Yes x B y Cổ z Cr a M b (wherein M represents at least one element selected from Nb and Mo, x, y, z, a, and b represent the atomic percentages of Si, B, Cu, Cr, and M, respectively; 11.0≦x≦17.0, 5.0≦y≦10.0, 0.5≦z≦2.0, 0.5≦a≦4.0, 1.0≦b≦5.0 And 65≦100-x-y-z-a-b≦75 is satisfied.) The composition is represented by A cut core characterized by:

2. At the contact surface, the soft magnetic alloy ribbon comprises: a substrate having the above-mentioned composition; an intermediate diffusion layer located outside the substrate, in which Si is enriched and Fe is depleted compared to the above-mentioned composition; and a surface oxide layer located outside the intermediate diffusion layer, which additionally contains O (oxygen) compared to the above-mentioned composition, in which Si is enriched and Fe and Cr are depleted. The cut core according to claim 1 .

3. The soft magnetic alloy ribbon contains an Fe-based nanocrystalline alloy. The cut core according to claim 1 .

4. The oxygen concentration at the outermost surface of the surface oxide layer is 43.0 atomic % or more. The cut core according to claim 2.

5. The impedance at a frequency of 100 kHz was measured before and after immersing the cut core in ion-exchanged water for 100 hours, and the measured value before immersion was Z A The measured value after immersion is Z B Then, (Z B -Z A ) / Z A The absolute value of the impedance change rate ΔZ calculated by × 100 is 15% or less. The cut core according to claim 1 .

6. the soft magnetic alloy ribbon is wound into a ring shape, and n laminates are formed by cutting the annular body at n locations (n ​​is an integer of 2 or more) perpendicularly to the circumferential direction of the annular body; the (n×2) cut surfaces of the n laminates serve as the contact surfaces; and two adjacent laminates of the n laminates come into contact with each other at the cut surfaces that serve as the contact surfaces, thereby forming a magnetic circuit as a whole. The cut core according to claim 1 .

7. The magnetic circuit comprises two or more laminates formed by providing a discontinuous portion at a portion of a circumference of one annular body formed by winding the soft magnetic alloy ribbon into a ring shape, at least one of two widthwise end faces of each of the two or more laminates serves as the contact surface, and two adjacent laminates of the two or more laminates contact each other at the widthwise end face serving as the contact surface such that the discontinuous portions do not overlap in the circumferential direction, thereby forming a magnetic circuit as a whole. The cut core according to claim 1 .

8. The cut core according to any one of claims 1 to 7 is used. Noise suppression material.

Citation Information

Patent Citations

  • Soft magnetic alloy

    JP1991075343A

  • Method for manufacturing high frequency core

    JP2001316724A

  • Corrosion resisting soft-magnetic alloy and its production

    JP1991024252A

  • Cut core and manufacture thereof

    JP1997027412A

  • Thin strip of soft magnetic alloy, method for manufacturing the same, and magnetic component having thin strip of soft magnetic alloy

    JP2011149045A